The Role of Occupational Medicine in Optimizing Bioethics in Breastfeeding for Female Worker - Dominiques Reggy Marfilan; Ray Wagiu Basrowi (The Indonesian Journal of Community and Occupational Medicine, 2024)
Introduction: Mother’s milk provides many benefits for babies. Breast milk is also one of the most complete and perfect foods for babies. Breast milk contains minerals, carbohydrates and fats in sufficient quantities to provide adequate nutrition for babies. Babies who are given breast milk can increase the baby’s resistance (immunity), thus preventing the baby from being attacked by infectious diseases such as diarrhea, pneumonia, measles and others. It is highly recommended to start giving breast milk as soon as the baby is born until the age of 4-6 months. Giving breast milk to babies can also prevent babies from stunting. Stunting is defined as the condition of children aged 0-59 months, where the height for age is below minus 2 standard deviations (<-2SD) from the WHO median standard.Methods: This studied obtained from four electronics journals, that obtained from google schoolar, CORE, and MKMI journal that published in Indonesian and English languages, between March 2018 untill January 2022. Only research and original studies are inclose experimental and observational methods, and secondary data.Results: Results of research obtained showed that according to the applicable regulations, breastfeeding and exclusive breastfeeding for working women is permitted and almost all workplaces allow female workers to carry out these activities. The importance of providing a breast milk room in a place of work will make it easier for working mothers to provide nutrition for their infant children. Breast milk is very important for these infant children.Conclusion: The importance of breastfeeding avoids malnutrition in babies and is protected by law so there are no prohibitions on preventing it.